Disrupted macrophage autophagy as a driver of cell death and LPS-induced lethal shock in systemic inflammation - Chekroune, Tarek; Carignon, Sandra; Taleb, Meriem; Savigny, Florence; Rose, Stéphanie; Maillet, Isabelle; Mura, Catherine (Frontiers in Immunology, 2025)
Systemic inflammatory response syndrome (SIRS) can be primed by infectious or non-infectious stimuli and may progress to life-threatening organ failure. An altered balance between pro- and anti-inflammatory response is commonly observed in SIRS, yet the core molecular events driving severe SIRS remain poorly defined. Moreover, the roles of macrophages and autophagy in SIRS have been pointed out. Here a high susceptibility to LPS-induced lethal shock in mice deficient in autophagy in myeloid cells (Atg5f/fLysM-cre+) following a single dose of 0.5 mg/kg (60% mortality vs. 0% in wild type after 24h) was observed. Using a very low dose of LPS (0.1 mg/kg), Atg5f/fLysM-cre+ mice showed rapid tissue injury, notably in the liver and spleen, accompanied by an altered macrophage phenotype. Macrophages in the spleen and the liver appeared swollen and showed a loss of cellular content, including iron. In contrast, hepatocytes in Atg5f/fLysM-cre+ mice accumulated more iron, which was associated with elevated reactive oxygen species levels compared to wild-type mice. Notably, the livers of LPS-treated Atg5f/fLysM-cre+ mice exhibited increased ferroptotic and apoptotic cell death and extensive pyroptosis in both the spleen and liver. Flow cytometric analysis, immunofluorescence, and RNA sequencing supported the marked pro-inflammatory phenotype of macrophages in LPS-treated Atg5f/fLysM-cre+ mice. In conclusion, during LPS-induced inflammation, autophagy deficiency in myeloid cells profoundly alters macrophage phenotype, disrupts iron trafficking, and promotes tissue injury through multiple forms of cell death.